2017
DOI: 10.1016/j.jiec.2017.03.042
|View full text |Cite
|
Sign up to set email alerts
|

New insights into surface-functionalized swelling high charged micas: Their adsorption performance for non-ionic organic pollutants

Abstract: The major components of the wastewater from the petroleum refineries are benzene, toluene and phenol and one of the techniques applied to the treatment of effluents is sorption using organo-functionalized clay. The materials exploited in the present study are a family of surface-functionalized synthetic micas and their sorption capacities for non-ionic organic pollutants are analyzed. The organo-functionalization of their surface provides them the capacity to sorb effectively non-ionic pollutants in the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…These swelling high charged micas, in which the layer charge can be adjusted, could be highly valuable for the decontamination of harmful metal cations via ion-exchange reactions [5] and for the selective removal of highly radioactive ions [6,7] and hydrocarbon molecules [8,9]. In fact, those synthetic micas overcome some limitations of the natural clay minerals to be used as host materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These swelling high charged micas, in which the layer charge can be adjusted, could be highly valuable for the decontamination of harmful metal cations via ion-exchange reactions [5] and for the selective removal of highly radioactive ions [6,7] and hydrocarbon molecules [8,9]. In fact, those synthetic micas overcome some limitations of the natural clay minerals to be used as host materials.…”
Section: Introductionmentioning
confidence: 99%
“…Organoclays have important applications as adsorbents of organic pollutants [13] and as components for the formation of clay polymer nanocomposites [10,14]. In concrete, the organo-functionalized synthetic swelling micas with long chain alkylammonium cations have shown a good adsorption capacity of nonionic hydrocarbons [9]. Stability on solution of clay minerals and the transition between stable colloidal dispersions and coagulated or flocculated systems are decisive processes for their applications in several industrial processes as well as in soil chemistry and environmental science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their physical and chemical properties can be easily tuneable by an appropriate synthesis method 4043 . These synthetic clay minerals have been successfully applied for the selective removal of heavy metals 40 , highly radioactive ions 44,45 and hydrocarbon molecules after an appropriate surface modification 46,47 . In fact, they overcome the limited CEC and adsorption capacity of natural nanoclays, and, in particular, organo-functionalized swelling high charged micas have already shown their excellent sorption capacity for the non-ionic organic pollutants benzene, toluene and phenol 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike phlogopite, these materials have significant swelling capabilities and applications as decontaminants and storage media (Alba et al, 2006;Gregorkiewitz and Rausell-Colom, 1987;Park et al, 2002). These swelling high-charged micas, in which the layer charge can be adjusted, may be valuable for the decontamination of harmful heavy metal cations (Ravella et al, 2008) via ion-exchange reactions and for the selective removal of radioactive ions (Alba et al, 2006) and hydrocarbon molecules (Alba et al, 2011) (Pazos et al, 2017). Recently, it has been observed that the formation of Inner Sphere Complexes (ISC) by the cations in the interlayer space of swelling high charge mica was favored when the aluminum content in the tetrahedral layer increased (Pavón et al, 2014).…”
Section: Introductionmentioning
confidence: 99%